Foreign Portfolio Investment And Human Capital Development In Nigeria 2005-2019 - Ighoroje, James Ese; Emmanuel, Akpokerere Othuke (Archives of Business Research, 2020)
Following the saving – investment gap resulting from shortfalls of savings suffered by developing economies it has become fashionable to embrace foreign capital inflow as an essential complementing alternative supply of funds for domestic investment. This study investigates the effect of foreign portfolio investment on human capital development in Nigeria covering the period 2005-2019. Foreign portfolio investment, the explanatory variable is disaggregated intoforeign portfolio equity (FPIE) and foreign portfolio bonds (FPIB), while exchange rate is included as the control variable. The Human Capital Development – the dependent variable is represented by the Human Development Index (HDI). Econometric techniques,including Descriptive Statistics,Augmented Dickey Fuller tests for unit roots, Error Correction Model (ECM), and Ordinary Least Square (OLS) Regression analysis were used. The study showed foreign portfolio investment in equity has positive and significant effect on human capital development while foreign portfolio investment in bonds has positive but insignificant effect. The study thus concluded that foreign portfolio investment has positive effect on human capital development and has helped to improve human capacity necessary for economic development in Nigeria. The study reiterated the need for eye-catching polices that will attract greater foreign portfolio investment in both equity and bonds in the stock market which could be achieved by greater openness.